Implementation of Active Knowledge Sharing Strategy to Improve Fikih Learning Outcomes - Ihwan Mahmudi; Dyah Purnama Ketty; Shafwatul Widad (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2022)
A good teacher is one who always has innovation and variety in teaching in order to achieve good learning outcomes. Fikih learning in the class one intensive F is less than optimal, as we know the average value limit in this Boarding School is 4.9 but class 1 is intensive f only achieved a score of 4.48, there are 26 students out of 38 students who have not graduated or 68.42 % and only 12 students who have graduated or 31.57 %. This is because the teacher's teaching strategy is monotonous. Based on this problem the research want to discuss about Active Knowledge Sharing learning strategy to teach fikih lesson.1. For knowing enhancement liveliness study student KMI class 1 intensive F in fikih lesson, 2. For knowing enhancement results, study KMI class 1 intensif in fikih lesson. This type of study is called Classroom Action Research (CAR). By following Kurt Lewin's model. Classroom Action Research is implemented in 2 cycles: planning, implementation, observation, and reflection. Research results are 1. Implementing an Active Knowledge Sharing strategy can increase learning results, and 2. Active students. In the first cycle, the results of liveliness among students reached 77.27%, then increased in the second cycle by 79.15%. Learning outcomes in the first cycle reached 84.84%, and in the second cycle increased by 93.93%. Based on this study.